Policy implications for awareness gaps in antimicrobial resistance (AMR) and antimicrobial use among commercial Nepalese poultry producers - Anastasia S. Lambrou; Gabriel K. Innes; Laura O'Sullivan; Himal Luitel; Rebanta K. Bhattarai; Hom B. Basnet; Christopher D. Heaney (BMC, 2021)
Abstract Background Nepal's poultry industry has increased with a growing middle class, which has translated to an increase in antimicrobial consumption and thus a rise in antimicrobial resistance (AMR). Describing and understanding antimicrobial use practices among commercial poultry producers in Nepal may help minimize the risks of AMR development in both humans and animals and determine the effectiveness of relevant policies. Methods From July to August 2018, poultry farmers were randomly recruited from Nepal's Chitwan District to participate in a cross-sectional study. The lead producer in each poultry operation was administered a quantitative structured-survey via a 30-min interview. Participants were asked to provide demographics, production practices, and knowledge about their antimicrobial use practices. Descriptive data analysis was performed to obtain frequencies and compare practices. Results In total, 150 commercial poultry producers of whom raised between 300 and 40,000 birds completed the interviews. Only 33% (n = 49) of producers reported knowing what AMR was, and among them only 50% (n = 25) consulted a veterinarian for treatment options. Antimicrobial administration for growth promotion was still employed by 13% of poultry producers. Similarly, critically important antimicrobial drugs, specifically colistin, were identified at 35% of participating operations. Producers reported low overall understanding and compliance of withdrawal periods (n = 41; 27%), which may result in both AMR development and adverse health reactions among consumers who ingest antimicrobial residues. Although Nepal has publicized antimicrobial use policies and awareness campaigns to instill healthy production practices, most producers (82%) were unaware of them. Conclusion Many Nepalese poultry producers lack overall antimicrobial use and AMR awareness, which is evidenced by low antimicrobial withdrawal period compliance, use of antimicrobials for growth promotion, and the sustained use of critically important antimicrobials. Improved outreach and educational capacities, paired with increased veterinary resources and extensive monitoring in operations and retail meat products, may increase AMR awareness and policy enforcement.